Revealing the hydrothermal crystallization mechanism of ilmenite-type sodium niobate microplates: the roles of potassium ions. Issue 40 (14th September 2017) - Gu, Qilin; Lu, Wanheng; Sun, Qiaomei; Zhu, Kongjun; Wang, Jing; Liu, Jinsong; Zhang, Jianhui; Zeng, Kaiyang; Wang, John
Abstract : The roles of K ions in the hydrothermal crystallization process of plate-like NaNbO3 microcrystals were revealed. Abstract : In this study, ilmenite-type NaNbO3 microplates were prepared by a facile surfactant-free method, using NaAc and KOH as a sodium resource and as a mineralizer, respectively. The effects of each reactant were identified, and the formation process and crystallization pathway of ilmenite-type NaNbO3 microplates were explored based on the phase constitution, microstructure and chemical compositional analysis. The indispensable roles of K ions, which participated in the formation of layered KNN-hydrate intermediates, were revealed. Ilmenite-type NaNbO3 microplates were formed by the dissolution of these intermediates and subsequent recrystallization into K-containing NaNbO3, followed by the ion-exchange between K and Na ions. Meanwhile excess K ions would hinder the release of K ions associated with the dissolution of intermediates, thus preventing the formation of ilmenite-type NaNbO3 . Moreover, the morphological evolution of ilmenite-type NaNbO3 microplates from platelets to octahedra was interpreted in terms of their intrinsic structure and KOH concentration.